PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MENGGAMBAR DEKORATIF SISWA KELAS III SDN 053 PEKANBARU - Suri, Milda Suri; Antosa, Zariul Antosa; Kurniaman, Otang Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Direct instructional model is one approach to teaching that is designed specifically to support the students' learning process related to dekratif knowledge and procedural knowledge are structured to teach the pattern of activity that gradually, step by step. The objective of this research is to improve the skills of students Decorative Drawing Class III SDN 053 Pekanbaru Application of Direct Learning Model. Subjects in this study is the third grade students of SDN 053 Pekanbaru academic year 2013/2014 the number of students 23 people. Formulation of the problem in this study is Are Applying Direct Learning Model to Enhance Skills Decorative Drawing Class III students of SDN 053 Pekanbaru ?. This research was conducted in the second cycle, the first cycle of meetings held three times and cycle II also held three meetings. Instrument data collection in this study is the observation drawing teacher, student observation sheet, rublik rublik assessment and product assessment process. The study is in the form of classroom action research (PTK). These results indicate that the Application of Direct Learning Model Decorative Drawing Skills To Enhance Student Class III SD Negeri 053 Pekanbaru. On preliminary data the average value of 42.39 decorative drawing skills students in the first cycle the average value of 68.65 students and an increase of 26.26 from the initial data. Meanwhile in the second cycle students' average score increased to 89.10 and increased by 20.45 from the cycle I. This suggests that Implementation of Direct Learning Model to Improve Student Skills Decorative Drawing Class III SD Negeri 053 Pekanbaru. Keywords: Direct Learning Model, Decorative Drawing Skills